The Effect of Financial Disclosure Regulation on Security Market Behavior. - Ingram, Robert W.; Chewning, Eugene G. (The Accounting Review, 1983)
ABSTRACT: This study reports on an empirical test of the effects of the Securities Act of 1933 and the Securities and Exchange Act of 1934 on investor behavior as revealed by security returns. The study differs from previous research into the effects of the Acts primarily by examining the percentage of annual cumulative abnormal returns that occurred during each month of test periods for years before and after the Acts. For firms with positive cumulative abnormal returns, aggregate market responses occurred earlier during fiscal years of the pre-Act periods tested (1926-1933) than during the fiscal years of post-Act periods tested (1935-1940). These results were robust to a variety of sampling and testing procedures. Implications and limitations of the study are discussed.